Cyber security in parallel and distributed computing : concepts, techniques, applications and case studies - Le, Dac-Nhuong; Kumar, Raghvendra; Mishra, Brojo Kishore; Khari, Manju; Chatterjee, Jyotir Moy (John Wiley & Sons, 2019)
The main objective of this book is to explore the concept of cybersecurity in parallel and distributed computing along with recent research developments in the field. It also includes various real-time/offline applications and case studies in the fields of engineering and computer science and the modern tools and technologies used. Information on cybersecurity technologies is organized in the fifteen chapters of this book. This important book cover subjects such as: Research and solutions for the problem of hidden image detection Security aspects of data mining and possible solution techniques A comparative analysis of various methods used in e-commerce security and how to perform secure payment transactions in an efficient manner Blockchain technology and how it is crucial to the security industry Security for the Internet of Things Security issues and challenges in distributed computing security such as heterogeneous computing, cloud computing, fog computing, etc. Demonstrates the administration task issue in unified cloud situations as a multi-target enhancement issue in light of security Explores the concepts of cybercrime and cybersecurity and presents the statistical impact it is having on organizations Highlights some strategies for maintaining the privacy, integrity, confidentiality and availability of cyber information and its real-world impacts such as mobile security software for secure email and online banking, cyber health check programs for business, cyber incident response management, cybersecurity risk management Security policies and mechanisms, various categories of attacks (e.g., denial-of-service),  global security architecture, along with distribution of security mechanisms Security issues in the healthcare sector with existing solutions and emerging threats.